La dimensione collaborativa tra soggetti pubblici e tra soggetti pubblici e privati nel contesto della cybersicurezza - Terracciano, Simona (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2025)
Considering the increase in hostile cyber activities targeting the digital infrastructures of public entities, it is necessary and urgent to establish an institutional framework capable of intercepting cyber threats preventively and intervening effectively to prevent or mitigate the damage from cybersecurity incidents and cyberattacks that affect fundamental public and private interests and the regular provision of public services. In this regard, the contribution analyzes some aspects of the collaboration between public entities and between public and private entities in the field of cybersecurity, focusing on recent regulatory interventions in the Italian legal system to verify if and how the Italian legislator intends to promote collaboration both in organizational and procedural terms, and through a fruitful collaboration with private entities in the procurement of ICT goods and services by public administrations.